Protection of assets. - Walsh, Timothy J., 1927-; Healy, Richard J.; ASIS International (Alexandria, VA : ASIS International, 2011)
Designed for protection professionals and all business managers with asset protection responsibilities. Includes pertinent studies, doctrine, practices, and industry standards and/or guidelines, as well as security theories, concepts, and solutions.
[1]. Information security -- [2]. Investigation -- [3]. Security officier operations -- [4]. Crisis management -- [5]. Security Management -- [6]. Physical security -- [7]. Applications -- [8]. Legal issues -- [9]. Cumulative index 2012.
"Founding authors ... Timothy J. Walsh, CPP, Richard J. Healy, CPP."--P. [iii].
Errata slip tipped-in.
Includes a cumulative index for all volumes [v.9].
Includes bibliographical references and index.
Also published in electronic format.
oif 03/12/14
Keywords: Industries -- Security measures -- Handbooks, manuals, etc